A review on Lantana rhodesiensis Moldenke: traditional uses, phytochemical constituents and pharmacological activities - BANGOU Mindiédiba Jean; MEDA Roland Nâg-Tiero; KIENDREBEOGO Martin; NACOULMA Odile Germaine; ALMARAZ-ABARCA Norma (International Journal of Phytomedicine, 2017)
Lantana rhodesiensis Moldenke an herbaceous, belonging to the Verbenaceae family is widely used in Africa folk medicine for the treatment of cancer, measles, malaria, smallpox, strength, coughs, fever, rheumatism, body pains, diabetes mellitus arrhythmia, parasitic diseases, arterial hypertension, old diarrhoeas. Many studies have been conducted on the chemical composition of the whole plant of L. rhodesiensis as well as biological activities. The aim of the present review was to give a detailed literature survey on its traditional uses, phytochemistry and therapeutical properties of L. rhodesiensis.